2018
DOI: 10.1111/1747-0080.12450
|View full text |Cite
|
Sign up to set email alerts
|

Dietetics workforce preparation and preparedness in Australia: A systematic mapping review to inform future dietetics education research

Abstract: This review provides a map for dietetics educators and researchers in Australia to guide future research regarding the preparation and preparedness of dietitians. Advancing the Australian dietetics workforce of the future will require a strategic, coordinated and collaborative approach to address the research gaps identified in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 74 publications
(89 reference statements)
1
31
0
Order By: Relevance
“…Dietetics students are well-placed to share their insights into the phenomenon of workforce preparation and are a widely researched group. A recent review of research in dietetics workforce preparation found that students were the most frequently studied of all participant groups (33) . However, much of the research to date has taken a piecemeal approach and focused on single, selected aspects of student's educational experiences; for example, assessment (34) , simulation (35,36) , problembased learning (37) , interprofessional learning (38,39) , clinical activities (40)(41)(42) , volunteering (43) , research (44,45) and reflective practice (46,47) .…”
Section: Introductionmentioning
confidence: 99%
“…Dietetics students are well-placed to share their insights into the phenomenon of workforce preparation and are a widely researched group. A recent review of research in dietetics workforce preparation found that students were the most frequently studied of all participant groups (33) . However, much of the research to date has taken a piecemeal approach and focused on single, selected aspects of student's educational experiences; for example, assessment (34) , simulation (35,36) , problembased learning (37) , interprofessional learning (38,39) , clinical activities (40)(41)(42) , volunteering (43) , research (44,45) and reflective practice (46,47) .…”
Section: Introductionmentioning
confidence: 99%
“…Further, dietetics practice educators are likely to be challenged by increasingly diverse and evolving practice landscapes, as recently described in Australia , the UK and the USA . Despite a lack of robust data on both the emerging and existing dietetics workforce in Australia , it has been suggested that new and emerging practice areas include private practice, the food industry and aged care , with private practice being reported as one of the dominant areas where Australian dietitians currently work (P. King, Dietitians Association of Australia, personal communication, 17 September 2018).…”
Section: Introductionmentioning
confidence: 99%
“…one city or state). Despite this existing body of evidence, there remains a lack of literature describing the perspectives of dietetics practice educators from a range of settings and geographical areas with respect to their overall experiences of preparing future dietitians .…”
Section: Introductionmentioning
confidence: 99%
“…A recent mapping review in one area of dietetics research, Australian workforce preparation, suggested that increases in dietetic training capacity have led to increased educational research output. It was estimated that in the last 30 years, more than half of the studies related to research in dietetics education were published in the period 2013‐2018 …”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that in the last 30 years, more than half of the studies related to research in dietetics education were published in the period 2013-2018. 5 Nutrition and dietetics research has been driven by advances in science and the development of new research methods, a process that has occurred parallel to the changing health-care environment and the context for dietetic practice. 6 However, the profile of research topics and methodological approaches employed by dietetic researchers has not previously been synthesised.…”
Section: Introductionmentioning
confidence: 99%